Synthesis, characterization and hydrogen storage characteristics of ambient pressure dried carbon aerogel - Singh S.; Bhatnagar A.; Dixit V.; Shukla V.; Shaz M.A.; Sinha A.S.K.; Srivastava O.N.; Sekkar V. (My University, 2025)
The present communication deals with the hydrogen storage performance of ambient pressure dried pristine as well as platinum doped carbon aerogel (CA-0.10 Pt). These carbon aerogels (CAs) have been prepared from resorcinol-formaldehyde (R-F) through sol-gel synthesis route with sodium carbonate as a catalyst (C). The synthesis parameters adapted led to the formation of CA having preponderance of submicropores. Structural and microstructural characteristics of these carbon aerogels have been investigated through XRD, SEM, TEM, nitrogen adsorption and Raman spectroscopic techniques. Nitrogen adsorption and TEM studies confirm the large density of micropores with the majority of pores having sizes between 0.30 and 1.46 nm (submicropores). The hydrogen storage characteristics of as synthesized carbon aerogels have been investigated by monitoring the hydrogen ad/desorption curves. At room temperature and at pressure upto 22 atm the CA and CA-0.1 Pt have hydrogen storage capacity of 0.40 wt.% and 0.33 wt.% respectively. However, under the same pressure but at liquid nitrogen temperature CA and CA-0.10 Pt have hydrogen storage capacity of 5.65 wt.% and 5.15 wt.%. Feasible reasons for the high hydrogen storage capacities at liquid nitrogen temperature for the present CAs have been put forward. Copyright © 2016 Hydrogen Energy Publications, LLC.